Static and dynamic analysis of three-layered partial-interaction composite structures. (1st February 2022) - Lin, Jian-Ping; Liu, Xiaolei; Wang, Yun; Xu, Rongqiao; Wang, Guannan
Highlights: Explicitly-formulated FEs are developed for the analyses of three-layered composite beams. The FE simulations are validated with good agreement and computational efficiency. The FEs are applied in the analysis of sandwich structures and corrugated steel-web bridges. Curvature locking phenomenon can be alleviated through introduction of internal DOFs. The importance of independent-rotation assumption among sub-elements is explained. Abstract: The static and dynamic behavior of three-layered composite structures is investigated in the present work through the presently proposed finite-element (FE) expressions. Relative to most research on partial-interaction composite beams, the present numerical method is developed through considering independently assumed interlayer slips and transverse shear deformations among sub-elements, the latter of which are based on the Timoshenko's beam theory. Variational method based on the minimum potential energy principle is delivered to establish the static and dynamic stiffness (and mass) matrices for the partial-interaction composite beams. The present results are validated against the analytical and numerical results from limited data presented in the literature where good agreement is generally obtained, giving credence of the present technique. What's more, the present FE technique is also demonstrated to be advantageous in the following sense: 1) The introduction of the internal degrees of freedom significantly alleviates the locking phenomenon that is frequently mentioned in the literature; 2) Independently assumed rotations for three layers are necessary in predicting the global behavior of composite structures with significantly distinct material properties. It is finally concluded that the developed FE framework provides a stable and efficient tool in investigating the three-layered composite beams/columns in various perspectives and could be readily extended to composite structures with more complex geometries or loading conditions.